If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -147 = 6x + -14 Reorder the terms: -147 + 13x = 6x + -14 Reorder the terms: -147 + 13x = -14 + 6x Solving -147 + 13x = -14 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -147 + 13x + -6x = -14 + 6x + -6x Combine like terms: 13x + -6x = 7x -147 + 7x = -14 + 6x + -6x Combine like terms: 6x + -6x = 0 -147 + 7x = -14 + 0 -147 + 7x = -14 Add '147' to each side of the equation. -147 + 147 + 7x = -14 + 147 Combine like terms: -147 + 147 = 0 0 + 7x = -14 + 147 7x = -14 + 147 Combine like terms: -14 + 147 = 133 7x = 133 Divide each side by '7'. x = 19 Simplifying x = 19
| 57-2x=7x+23 | | 7-9x=36-13x | | 6x+9=-17-7x | | -7x^2+52x-85=0 | | -x^2-4X=0 | | .6(d+3)=3d | | -x^2-3x+18=0 | | -x^2-4x-3=0 | | 7x-9=15+4x | | x^2+12x+33=0 | | 9a-7+a=14+3a | | 6y+12-9=15 | | 4b+2b=3b+36 | | 7x^2+38x+15=0 | | -x^2-9x-18=0 | | 9x-6x+2=23 | | 2x^2-3x-12=0d | | 5x^2-23x+24=0 | | 2x+3(1-2x)=3x-2 | | 3(2x+4)=4x+20 | | n^2+2n+93=0 | | 15+26x=-8x^2 | | 12(x+3)=4(3x+4)+20 | | n^2-4n+5=8 | | 0.30(6)+0.05x=0.15(12+x) | | 3x-4=-x+12 | | 15x+10-2x+12=15 | | 10x+x=3+x | | 11x-4(x-2)=7x+4 | | -(6y+4)-(-5y-5)=-3 | | 3y^2-26y-9=0 | | -3(x+5)= |